История и религия хазар в исследованиях Омеляна Прицака (к 100-летию со дня рождения) - Бубенок, О.Б.; Василюк, О.Д. (Хазарский альманах, 2020)
In 2019, the scholars from many countries celebrated the 100th anniversary of Omeljan Pritsak who was a famous historian and orientalist of the present. He was one of the largest experts in the Khazar studies. The academician A. Krymsky infl uenced on O. Pritsak’s interest to the studying of Khazar history. Further O. Pritsak used some parts from monograph “The History of Khazars” by A. Krymsky. During his Germany period O. Pritsak began to study the Khazar history. In the USA he continued the Khazar studies at Harvard University in 1964–1990. There he wrote the works on this topic. Among them are the monograph “Khazarian Hebrew Documents of the Tenth Century” (with N. Golb) and many papers. In 1991 O. Pritsak returned to Ukraine where he founded the A. Krymsky Institute of Oriental studies in the Ukrainian Academy of Sciences. As a result, the Khazar problems are submitted in the editions and conferences of the Institute of Oriental studies. In 1997 “Khazarian Hebrew Documents of the Tenth Century” was published in Russian. O. Pritsak wrote his last works on the Khazar problem in 1991–1998 during his new Ukrainian period.